Propagation of magnetoelastic waves in a periodic media - Papyan, A. A. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We consider a problem of elastic wave propagation in a perfectly conductive periodic structure in a external magnetic field. In the framework of the Floquet theory the dispersion equations are obtained defining magnetoelastic wave frequency gap bandstructure. The influence of an external magnetic field on the magnetoelasic wave properties and forbidden frequencies arestudied. Рассматривается задача распространения волн в одномерной периодической электропроводящей среде, находящейся во внешнем постоянном магнитном поле. Задача решается на основе теории Флоке. Установлено влияние внешнего магнитного поля на условия существования запретных зон частот. Աշխատանքում ուսումնասիրվում է մագնիսաառաձգական ալիքների տարածումը միաչափ պարբերական կառուցվածքով ունեցող միջավայրերում: Ֆլոկեի տեսության շրջանակում ստացվել են դիսպերսիոն հավասարումները, որոնք որոշում են ալիքների բաց թողնման եւ կասեցման հաճախականության տիրույթները: Կատարված են դիսպերսիոն առնչությունների վերլուծություններ:
Keywords: Coupling of solid mechanics with other effects; Waves